PENGARUH METODE DRILL DAN LEG SWING TERHADAP SERVIS SEPAK TAKRAW - M. Fadli; Leo Pratama; Waskito Aji Suryo Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of combining the drill method and leg swing exercises on sepak takraw service ability among Physical Education students at UNIMUDA Sorong. Employing a quantitative experimental approach with a pretest-posttest control group design, this study involved 10 samples divided into an experimental group (n=5) and a control group (n=5). The intervention was administered over 12 sessions within a 4-week period. The instrument used was a service skill test assessing accuracy, speed, and consistency. Data analysis was conducted through the Shapiro-Wilk normality test, Levene's Test for homogeneity, paired sample t-test, independent sample t-test, and N-Gain test. The findings indicate that the drill method combined with leg swing exercises significantly affects service ability (p = 0.003 < 0.05). The experimental group achieved an average N-Gain of 0.572 (medium category), surpassing the control group which only reached 0.457 (medium category). Thus, this approach proves to be superior to conventional drill methods in enhancing service ability among Physical Education students at UNIMUDA Sorong.